Retracted: Knowledge, attitude, and practice of contraception among women attending a tertiary care hospital - Agrawal, Alpana; Saxena, Rashmi; Gupta, Manisha; Agarwal, Neelima; Shubham, Divya; Tyagi, Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The article "Knowledge, attitude, and practice of contraception among women attending a tertiary care hospital" is retracted by the Editor-in-Chief, due to violation of the policies and practices of International Journal of Reproduction, Contraception, Obstetrics and Gynecology. The article is retracted due to dispute in authorship.